(untitled) (Książnica Śląska, 2025)
The author presents the history of the Sądecka Public Library related to administrative changes. Against this background, she discusses regional bibliographic activity covering various territorial areas of the Sądecczyzna region. She recalls the first retrospective bibliography of Kazimierz Golachowski, further the bibliography of Władysława Lubasiowa, the bibliographic file of Stanisław Chrząstowski and materials published in regional magazines. The text describes the current bibliographic activities carried out within the Regional Bibliography of Małopolska.